2005
DOI: 10.1111/j.1439-037x.2005.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid Differentially Affects Growth, Ion Uptake and Abscisic Acid Concentration in Salt‐tolerant and Salt‐sensitive Rice Cultivars

Abstract: Phytohormones play critical roles in regulating plant responses to stress. Here, we investigated the effects of salt stress and stress recovery by applying jasmonate to the two different rice (Oryza sativa L.) cultivars Dongjinchalbyeo (DJC, salt-tolerant) and Dongjinbyeo (DJ, salt-sensitive). Salt stress remarkably decreased the root length of plants even at low NaCl concentration (20 mm). Salt stress led to a sharp increase in the concentrations of abscisic acid (ABA) in 20 and 40 mm NaCl, when compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(116 citation statements)
references
References 75 publications
(145 reference statements)
8
107
0
1
Order By: Relevance
“…The level of endogenous ABA was quantified by gas chromatography-mass spectrometry (GC-MS) as described previously [22][23][24][25][26]. Plants were immediately frozen in liquid nitrogen.…”
Section: Measurement Of Endogenous Aba By Gas Chromatography-mass Spementioning
confidence: 99%
“…The level of endogenous ABA was quantified by gas chromatography-mass spectrometry (GC-MS) as described previously [22][23][24][25][26]. Plants were immediately frozen in liquid nitrogen.…”
Section: Measurement Of Endogenous Aba By Gas Chromatography-mass Spementioning
confidence: 99%
“…However, it is becoming increasingly evident that these compounds have direct and/or indirect roles in abiotic stresses. Thus, several researches showed that JAs levels were increased upon exposure to drought and salt stresses [30] [13]. Some studies demonstrated that JA accumulation during drought is not stable; for example, water-stressed soybean plants exhibited a transient increase in JA, followed by a decrease to below wild-type levels [31].…”
Section: Effect Of Ja On Plant Growth Responses Under Drought and Salmentioning
confidence: 99%
“…Levels of ABA were measured following the method of Kang et al (2005). Approximately 0.1 g of S1 panicles was collected and extracted with an extraction solution containing 95% isopropanol, 5% glacial acetic acid, and an internal standard, [(6)-3,5,5,7,7,7-d 6 ]ABA.…”
Section: Measurements Of Meja and Abamentioning
confidence: 99%